Supply Chain 5.0: The Next Generation of Business Success through Customer Centricity, Sustainability & Human Rights and Digitalization - Jain, Prateek; Chou, Mabel C. (New Jersey: World Scientific, 2024)
(3z(BSupply Chain 5.0: The Next Generation of Business Success through Customer Centricity, Sustainability & Human Rights and Digitalization(3y (Bunveils a transformative era in supply chain management, presenting a groundbreaking business model that integrates three pivotal elements: Customer Centricity, Sustainability & Human Rights, and the interplay of Advanced Digitalization. This insightful book guides businesses through the evolving landscape, showcasing how they can synchronize these elements to revolutionize their operations and unlock unparalleled value, ensuring future success. As consumer expectations shift and the world demands responsible practices, embracing the new generation of Supply Chain isn$1 (Bt just an option b it$1 (Bs the only way for organizations to thrive and shape a profitable and sustainable future.s
Includes Index and afterword
Keywords: Business logistics; Supply chain management; Sustainable development; Digital transformation